Assessing Disability in Working Age Population : A Paradigm Shift from Impairment and Functional Limitation to the Disability Approach - Bickenbach, Jerome; Posarac, Aleksandra; Cieza, Alarcos; Kostanjsek, Nenad (World Bank, Washington, DC, 2015)
The objectives of this study are two-fold. First, it presents the basics of assessing working age populations for disability benefits. Increasingly, the operational staffs of the World Bank Group (WBG) and the World Health Organization (WHO), as well as of other development organizations, are being requested by governmental policy agencies for technical advice and assistance on how to reform their disability assessment system. Secondly, while acknowledging limitations, both in conception and implementation; it makes a case for why adopting the international classification of functioning, disability, and health (ICF) approach to disability assessment may be smart policy that corresponds well with the aims of modern disability policy that focuses on social and economic inclusion for individuals with disabilities, in the context of a recognition of their fundamental human rights. The study is a follow up work to the world report on disability that WHO and WB published jointly in June 2011. The world report made it clear that the process of disability assessment is an important lever of disability policy in any country, yet little is known about how disability assessment is conducted. This study responds to that knowledge gap, but it also describes a paradigm shift in the assessment of disability, one that moves from prevailing impairment and functional limitation approaches to a disability-based approach.